Elevated FISH Her-2/neu Amplification in ER Positive, IHC Her-2 Equivocal Invasive Breast Cancer Patients of North-East India - Baruah, Priyanki; Sarma, Anupam; Bhattacharyya, Mouchumee; Sarma, Pallavi; Das, Biki Chandra; Sarma, Dhrubajyoti; Tamuly, Monica; Talukdar, Abhijit; Das, Gaurav; Sharma, Swati; Kataki, Amal Chandra; Deka, Mrinal; et al. (Asian Pacific Journal of Cancer Care, 2024)
Background: Breast cancer management of Her-2 equivocal breast cancer patients requires assessment by fluorescent in situ hybridization (FISH) for Her-2/neu amplification. Assessment of FISH Her-2/neu amplification status in IHC Her-2 equivocal invasive breast cancer patients of North-East India. Methods: One hundred sixty-two (n=162) IHC Her-2 equivocal (2+) breast cancer patients were analysed by FISH for Her-2/neu amplification using PathVysion Her-2/neu DNA probe kit. The interpretation of FISH Her-2/neu amplification was based on ASCO/CAP 2018 guidelines. Results: FISH Her-2/neu amplification was detected in 59.26% (n=96) patients and 40.74% (n=66) patients had no amplification. There were 160 female and 2 male patients. ER-positive patients were 68.51% (n=111) and PR-positive were 54.93% (n=89). “ER+/PR+” status was found in 54.93% (n=89) patients whereas “ER-/PR-’’ in 31.48% (n=51) patients. Significant association was observed between histological grade and FISH Her-2/neu amplification (p=0.036). ER-positive patients had also shown significant association with FISH Her-2/neu amplification (p=0.039). ER+/PR+ patients had shown a trend for higher likelihood of FISH Her-2/neu amplification (p=0.053). There were no significant association observed between FISH Her-2/neu amplification with age (p=0.625), lymph node positivity (p=0.642), laterality (p=0.367), histopathology (p=0.226) and PR-positivity (p=0.199). Conclusion: FISH Her-2/neu amplification in IHC Her-2 equivocal breast cancer patients of North-East India was found to be significantly associated with ER-positive status and histological grade. ER+/PR+ patients have also an enhanced likelihood of FISH Her-2/neu amplification.